Diagnósticos de Influência em Modelo de Regressão de Valor Extremo em Censura Tipo I - Andrade, Maria Aparecida Silva de (2016)
In this paper, we analyze the problem of evaluating the influence of observations in the extreme value regression model (Gumbel regression) under type I censorship. This model is very important in the analysis of lifetime data. First, we obtain the log-likelihood function, the score function and Fisher's information matrix. Then we will discuss some methods of influence, such as global influence and the influence local. In the local influence analysis will derive the normal curvatures under various perturbation schemes. We conclude the work obtaining a closed-form expression for the generalized leverage.